Prospective paediatric intensive care registry in Latvia: one year outcomes - Veģeris, Ivars; Daukšte, Iveta; Bārzdiņa, Arta; Parslow, Roger C.; Balmaks, Reinis (Acta medica Lituanica, 2019)
Background. In Latvia, there is a single eight-bed paediatric intensive care unit (PICU) where all critically ill children are admitted. A recent retrospective audit of the outcomes of paediatric critical care in this unit revealed a high number of unplanned extubations and excess crude mortality. In 2017, our centre joined the UK and Ireland based Paediatric Intensive Care Audit Network (PICANet) as a pilot project to investigate the feasibility of developing a paediatric critical care registry in Latvia and in the Baltic states. Methods. Riga Stradins University Ethics Committee approved the study. Anonymized data on all patients admitted to our unit from 1 June, 2017 to 31 May 2018 were prospectively entered onto the PICANet database. Results. A total of 774 PICU admissions were analysed; 45% of admissions were elective. The median age was 59 months (IQR: 14–149). The highest admission rate was on Wednesdays representing the flow of elective surgical patients. The median length of stay was 0.95 days (IQR: 0.79–1.98). Twenty-five percent required respiratory support. The expected number of deaths estimated using the Paediatric Index of Mortality 3 (PIM 3) 15.16; 15 patients (1.94%) died resulting in Standartized Mortality Ratio (SMR) of 0.99 (95% CI 0.57–1.60). The emergency readmission rate within 48 hours after PICU discharge was 0.9%. There were 1.8 unplanned extubations per 100 invasive ventilation days. Other paediatric intensive care audit networks reported similar adjusted mortality rates but lower rates of unplanned extubations. Thirty days after PICU discharge, 653 (84.36%) patients were alive and outside hospital, 98 (12.66%) were inpatients, six (0.78%) had died, two (0.26%) were lost to the follow-up. We observed a marked peak of infant emergency respiratory admissions in February. Conclusions. This project explored the possibility of prospective paediatric critical care audit in Latvia by joining an established international network. This allowed direct comparison of outcomes between the countries. Excess mortality was not observed during one-year data collection period, however a high rate of unplanned extubations was revealed. The results allowed a better planning of elective patient flow by spreading elective cases over the week to avoid “rush hours”
Keywords: pediatric; critical care; intensive care